1996
DOI: 10.1071/mf9961009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sewage effluents on germination of three marine brown algal macrophytes

Abstract: Inhibition of germination of zygotes of the fucoid macroalgae Hormosira banksii and Phyllospora comosa and zoospores of the laminarian Macrocystis angustifolia was used as an end-point to assess the toxicity of three sewage effluents of differing quality. For each species, between-assay variation was low and results of tests with the reference toxicant 2,4-dichlorophenoxyacetic acid suggested that results are reproducible, especially in R. comosa. Each species showed a greater sensitivity to primary-treated ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…S. japonica has similar characteristics, as no survival of spores at salinities less than 5% were found. It has often been observed that reduced salinity exerts damaging effects on germination and embryo growth in many brown macroaglal taxa, by increasing osmotic pressure which results in disturbances in membrane permeability (Burridge et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…S. japonica has similar characteristics, as no survival of spores at salinities less than 5% were found. It has often been observed that reduced salinity exerts damaging effects on germination and embryo growth in many brown macroaglal taxa, by increasing osmotic pressure which results in disturbances in membrane permeability (Burridge et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Las aguas residuales alteran el contenido orgánico y la composición bioquímica de los sedimentos (Cotano y Villate 2006), así como las propiedades bioquímicas de la columna de agua (Oviatt et al 1987), afectando las comunidades biológicas mediante explosiones de algas consumidoras de nitrógeno (Thornberg et al 2008), concentraciones elevadas de patógenos y bacterias que pueden incorporarse a la cadena alimentaria (Korajkic et al 2010), erosión del arrecife por procesos mecánicos, bioquí-micos y biológicos (Pastorok y Bilyard 1985), cambios en la síntesis de proteínas y crecimiento (Houlihan et al 1994), cambios en las tasas de respiración y alimentación (Butler et al 1990) e inhibición de la germinación (Burridge et al 1996).…”
Section: Introductionunclassified
“…Estos trabajos han demostrado que los vertidos residuales pueden alterar patrones en la estructura de aguas y la diversidad de las comunidades afectadas, aunque los efectos pueden variar Influence of the combined disposal of sewage and brine on meiofauna Influencia de la combinación de vertidos de aguas residuales y salmuera sobre la meiofauna Guidetti et al 2003, Chapman et al 2005. Sewage discharges alter the organic content and biochemical composition of sediments (Cotano and Villate 2006), as well as the biochemical properties of the water column (Oviatt et al 1987), affecting biological assemblages through blooms of nitrogen-consuming algae (Thornberg et al 2008); high concentrations of pathogens and bacteria that may enter the food chain (Korajkic et al 2010); reef erosion by mechanical, chemical, and biological processes (Pastorok and Bilyard 1985); changes in protein synthesis and growth (Houlihan et al 1994); changes in feeding and respiration rates (Butler et al 1990); and inhibition of germination (Burridge et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Bellgrove et al (1997) suggested that absence of H. banksii in locations experiencing environmental pressure may be a result of competitive interaction with more opportunistic species such as Ulva and Enteromorpha. In addition, inhibited germination of H. banksii zygotes at locations receiving sewage effluent was demonstrated by Burridge et al (1996) with greater sensitivity of the species being displayed to poorer quality discharge. The absence of H. banksii throughout Sydney Harbour may be associated with sporadic contaminated freshwater input or be due to competition with other species.…”
Section: Bush Locations Were Dominated By Bembicium Auratum Saccostrmentioning
confidence: 99%